2016
DOI: 10.1108/mip-02-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-esteem, negative affect and normative influence in impulse buying

Abstract: Purpose – The purpose of this paper is to empirically examine the roles of self-esteem (SE), negative affect (NA), and consumer susceptibility to normative influence in the enactment of impulse buying behavior. Design/methodology/approach – A theoretical model is developed through an extensive review of literature. Survey research is conducted to collect the data from respondents. Structural equation modeling is performed to test the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 56 publications
4
41
0
5
Order By: Relevance
“…The results showed that there is a positive correlation to online impulse buying. Similar results were obtained by previous researchers (Bandyopadhyay, 2016;Mohan, Sivakumaran, & Sharma, 2013;Nayebzadeh & Jalaly, 2014), that impulse buying tendency positively affects impulse buying behavior. Chusniasari & Prijati (2015) found results that hedonic shopping has a significant and positive influence on impulse buying of Pointbreak Tunjungan Plaza Surabaya's customers.…”
Section: Hypothesis Testing Resultssupporting
confidence: 91%
“…The results showed that there is a positive correlation to online impulse buying. Similar results were obtained by previous researchers (Bandyopadhyay, 2016;Mohan, Sivakumaran, & Sharma, 2013;Nayebzadeh & Jalaly, 2014), that impulse buying tendency positively affects impulse buying behavior. Chusniasari & Prijati (2015) found results that hedonic shopping has a significant and positive influence on impulse buying of Pointbreak Tunjungan Plaza Surabaya's customers.…”
Section: Hypothesis Testing Resultssupporting
confidence: 91%
“…For instance, based on Indian samples, Mohan et al (2013) found that the relationship between negative affect and impulsive buying is not significant. Both Bandyopadhyay (2016) and Liu et al (2019) confirmed that negative affect can stimulate impulsive buying, while Bellini et al (2017) indicated that negative affect may inhibit impulsive buying. Hence, further examination of this issue is imperative, in view of these contradictory empirical evidences.…”
Section: Information Anxiety and Impulsive Buyingmentioning
confidence: 89%
“…Impulsive buying has been loosely defined in literature as spontaneous, immediate, and unplanned purchase (D'Antoni Jr & Shenson, 1973;Rook & Fisher, 1995;Stern, 1962), often triggered by stimuli (Rook, 1987). Prior research found that impulsive buying is driven by a variety of psychological factors, such as affect, or affective state (Bellini, Cardinali, & Grandi, 2017;Mohan, Sivakumaran, & Sharma, 2013;Verplanken et al, 2005), impulse tendency (Lucas & Koff, 2017;Nagar, 2016), self-esteem (Bandyopadhyay, 2016), self-identity and self-image (Lucas & Koff, 2017), upward social comparison (Liu, He, & Li, 2019), long-term orientation (Aparecida Lehmann, Krug, & Falaster, 2019), and aspects of the big five personality factors (Bratko, Butkovic, & Bosnjak, 2013). By reviewing the extant literature, it can be clearly found that impulsive buying is an emotion-related behavior.…”
Section: Information Anxiety and Impulsive Buyingmentioning
confidence: 99%
“…He posited that exposure to impulse stimuli brings in individuals affective reactions and individuals feel sudden spontaneous urge or impulse to buy something. If the urge is stronger than the willpower of individuals (to restrain buying urge), impulse buying gets exhibited unless thwarted by situational impediments (Dholakia, 2000;Beatty and Ferrell, 1998;Bandyopadhyay, 2016). In the words of Beatty and Ferrell (1998), "felt urge to buy impulsively is a state of desire that is experienced upon encountering an object in the en environment.…”
Section: Perceived Crowdingmentioning
confidence: 99%
“…I include urge to buy as the proximal determinant of the act of impulse buying. Impulse buying can't take place without the generation of uncontrollable impulsive urges in response to stimuli (Hoch and Lowenstein, 2011;Beatty and Ferrell, 1998;Mohan et al, 2013;Bandyopadhyay, 2016).…”
Section: Introductionmentioning
confidence: 99%